Determinants of Zero Waste Lifestyle Adoption Among Generation-Z - Pratiwi, Putu Yani; Handra, Tessa; Choirisa, Septi Fahmi (ADI Publisher, 2021)
Research on green consumption has two streams, the stream about how consumers consume green products (consume differently) and the stream about how to consume less. Most research focus on the stream about consume differently, therefore this study would like to contribute to the latter research stream by understanding the determinants of zero waste lifestyle adoption. The 3R theory (Reduce, Reuse, Recycle) is used in this study. The object of this study is generation-Z who live in Indonesian big cities, aged between 15 - 24 years. Data collection is done by using online questionnaire to 322 respondents. This study uses descriptive research design and judgemental sampling to collect the data. Data analysis is done by using structural equation modelling. Variables used in this study are attitude toward zero waste lifestyle, social norm, personal norm, altruistic motivation, and social media activity. The findings of this study are social media activity significantly influence reduce, reuse, and recycle behavior, social norms significantly influence recycle behavior only, while other factors do not significantly influence zero waste lifestyle adoption of generation-Z. This study gives insight that social media has significant role in changing consumer behavior to be more sustainable.